ANALISIS HUKUM DAMPAK BELUM DIRATIFIKASI KERANGKA KERJA KONVENSI PENGENDALIAN TEMBAKAU (FRAMEWORK CONVENTION ON TOBACCO CONTROL) BAGI INDONESIA - santoso, aditia bagus; edorita, widia; diana, ledy (Lampung University, 2014)
Framework Convention on Tobacco Control (FCTC) is an international treaty for tobacco control efforts for world health under the WHO. Indonesia has not ratified the treaty as far as the impact that would be acceptable for Indonesia, while many countries in the world have ratified and observed what steps should be taken in the case of the strategic Indonesia.Â Keywords: Impact, Ratification, Framework Convention On Tobacco Control